Pengaruh Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan pada Dinas Perkebunan Kabupaten Fakfak - Maria Wesso; Agustina Waromi; Fenska Mbaubedari (International Forum of Researchers and Lecturers, 2025)
This study aims to examine the influence of motivation and work environment on employee performance at the Plantation Office of Fakfak Regency. A quantitative structural approach was used with a sample of 50 employees selected purposively. Data were collected through interviews, questionnaires, and documentation, then analyzed using descriptive and inferential statistics via SmartPLS 3.8. The results showed that work motivation (80.55%), work environment (86.8%), and employee performance (79.91%) were all rated as good. Partial tests revealed that motivation significantly influenced performance (t = 2.341; p = 0.024), as did the work environment (t = 3.694; p = 0.001). Simultaneous testing using ANOVA produced an F value of 39.120 with a significance level of 0.000 (<0.05), indicating a significant combined effect. The coefficient of determination (R²) was 0.700, suggesting that 70% of the variance in employee performance is explained by motivation and work environment, while the remaining 30% is influenced by other factors not examined in this study. It is recommended that the Plantation Office of Fakfak Regency improve motivation and work conditions to further enhance employee performance.